Standards in the real estate industry. - Mittal, Kunal
The fever for new XML specifications for almost anything imaginable has hit the real estate industry. Companies that are actively pursuing some niche in this industry have realized the need to create and adopt standards for communication. As in other industries, however, competing XML standards for emerging, keeping any one standard from reaching a critical mass of adoption and fruition.